The Late 1990's Financial Crisis in Ecuador : Institutional Weaknesses, Fiscal Rigidities, and Financial Dollarization At Work - Jacome, Luis. (Washington, D.C. : International Monetary Fund, 2004)
This paper stresses three factors that amplified the 1990s financial crisis in Ecuador, namely institutional weaknesses, rigidities in public finances, and high financial dollarization. Institutional factors restricted the government's ability to respond in a timely manner and efficiently enough to prevent the escalation of the banking crisis and spurred the adoption of suboptimal policy decisions. Public finance rigidities limited the government's capacity to correct existing imbalances and the deteriorating fiscal stance associated with the costs of the financial crisis. Financial dollarization increasingly reduced the effectiveness of financial safety nets, fostered foreign currency demand, and accelerated a currency crisis, thereby further worsening the solvency of banks. These three factors reinforced each other, exacerbating costs as the economy went through a triple banking, currency, and fiscal crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet